2010
DOI: 10.1002/adsc.201000575
|View full text |Cite
|
Sign up to set email alerts
|

Dimethyl Sulfoxide/Potassium Hydroxide: A Superbase for the Transition Metal‐Free Preparation of Cross‐Coupling Products

Abstract: Potassium hydroxide (KOH) in dimethyl sulfoxide (DMSO) forms a superbasic medium that allows one to access cross-coupling products from reactions between aryl halides with various sulfur-, oxygen-and nitrogen-based nucleophiles under transition metal-free conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
60
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(63 citation statements)
references
References 91 publications
2
60
0
Order By: Relevance
“…Electrophilic coupling partners have only stable functional groups such as methyl, methoxy, fluoride, amino, nitro, and hydroxy. 15 For control experiment, reaction of chlorobenzaldehyde and ethyl 4-chlorobenzoate with benzenethiol using KOH/DMSO at 130°C was carried out, providing the corresponding sulfide in low yield.…”
Section: A12mentioning
confidence: 99%
“…Electrophilic coupling partners have only stable functional groups such as methyl, methoxy, fluoride, amino, nitro, and hydroxy. 15 For control experiment, reaction of chlorobenzaldehyde and ethyl 4-chlorobenzoate with benzenethiol using KOH/DMSO at 130°C was carried out, providing the corresponding sulfide in low yield.…”
Section: A12mentioning
confidence: 99%
“…Strong bases, such as isopropylmagnesium chloride or hexyllithium, are required. Other reaction conditions, such as sulfur in KOH/ DMSO (Yuan et al, 2010), K 2 CO 3 /MeOH (Ansell et al, 1970) or Et 3 N/pyridine (Becker et al, 1973), did not yield the desired product.…”
Section: Structure Descriptionmentioning
confidence: 97%
“…However, we never experienced selectivity problems, even at elevated temperatures. [18] Concerning the possibility of free-radical S N Ar mechanisms (S RN 1), radical scavengers TEMPO, galvinoxyl and acrylonitrile failed to inhibit the reactions shown in Table 2, suggesting that radicals are not involved.…”
mentioning
confidence: 99%
“…It was observed that an elevated temperature (145 °C) is necessary to furnish the desired diaryl ether 11 in moderate to excellent yields (Table 2, entries [16][17][18]. When the reactions were repeated at 120 °C with the 3 aryl halides, the best conversion was obtained in the case of 4-bromoacetophenone, while 4-iodo and 4-chloroacetophenone gave modest results (Table 2, entries 16'-18').…”
mentioning
confidence: 99%
See 1 more Smart Citation